The Postnatal Subventricular Zone: A Source of New Cells in This Old Brain - Bordey, Angélique (Nepal Journal of Neuroscience, 2005)
Findings over the past decades demonstrating persistent neurogenesis in the adult brain have challenged the view of a fixed circuitry and raise hopes for self-renewal following brain injury. The subventricular zone (SVZ, also called subependymal layer, SEL) lining the lateral wall of the lateral ventricle is the largest germinal center where stem cells displaying astrocytic traits have been identified. These astrocyte-like cells ensheath neuroblasts, which migrate throughout the SVZ and along the rostral migratory stream to the olfactory bulb where they differentiate into interneurons. The cellular architecture of the SVZ has been essential for the development of hypotheses to explain how intercellular signaling and non-synaptic communication could regulate neurogenesis. An array of signaling molecules have recently been identified that may offer future strategies to promote neurogenesis and reroute neuroblasts to higher cognitive centers. Nepal Journal of Neuroscience, Volume 2, Number 1, 2005, page: 12-23